Isolation of Oxoaphorpine Alkaloid from Bark of Cryptocarya Ferrea - Saidi, Nurdin; Awang, Khalijah; Yahya, Mustanir (Emanuscript Services, 2019)
Extraction, isolation, identification and characterization of the compounds isolated from the bark of Cryptocarya ferrea yielded three known oxoaphorpine alkaloids. They are o-metilmoschatoline 1, ateroline 2 and subsesiline 3. Structural elucidation was established through spectroscopic methods 1D-NMR and 2D-NMR, UV, IR, and Mass Spectrometry and comparison with the published data. © 2019 Phcogj.